Income Analysis of Industrial Plantation Forest (HTI) Laborers as Edible-Nest Swiftlet Farmers in Sungai Batang Village, Air Sugihan District, Ogan Komering Ilir Regency - Saputra, Doris; Elmeizy Arafah; Yuwinti Nearti; Budi Fachrudin; Nirmala Jayanti; Ismail (KaliAgri Journal, 2025)
Edible bird’s nest is a high-value commodity with strong export demand, which encourages the growth of swiftlet farming as an alternative livelihood in rural areas. This study aims to analyze the income level of Industrial Plantation Forest (HTI) laborers who operate edible-nest swiftlet farming in Sungai Batang Village, Air Sugihan District, Ogan Komering Ilir Regency. A case study method was applied from November 2018 to March 2019 involving 10 respondents (census). Income analysis was conducted by calculating production costs, total revenue, net income from swiftlet farming, and total household income (swiftlet income plus HTI wage income). The results show that average annual revenue from swiftlet farming reached IDR 33,220,000 with total production cost of IDR 14,832,067, producing a net income of IDR 18,387,933/year. Meanwhile, HTI labor income was IDR 11,500,000/year. Therefore, total household income amounted to IDR 29,887,933/year. These findings confirm that swiftlet farming contributes dominantly to household income structure and serves as an effective rural income diversification strategy.